MEMBANGUN KECERDASAN EMOSIONAL MELALUI LIFE SKILL MANAJEMEN EMOSI DALAM KEGIATAN PIK-R DI SMP NEGERI 22 SEMARANG - Anggir Palupi, Astri; Wahyu Wardhani, Novia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is grounded in the importance of developing students’ emotional intelligence as a foundation for character formation in the school environment. Through the Youth Information and Counseling Center (PIK-R), the school organizes emotional management life skill activities to equip students in dealing with social dynamics and peer pressure. This study aims to analyze the implementation and impact of emotional management life skills in fostering students’ emotional intelligence and its implications for strengthening moral intelligence and character at SMP Negeri 22 Semarang. The study employs a descriptive qualitative approach using observation, interviews, and documentation to collect in-depth data. PIK-R administrators delivered the material through interactive sessions, including concept presentations, group discussions, educational games, and question-and-answer activities. The program encourages students to recognize their emotions, regulate their responses effectively, understand others’ feelings, and develop positive peer communication. Although not all students demonstrated optimal participation, the activity provided initial experiences that enhanced self-awareness, emotional regulation, empathy, and social skills. Overall, the emotional management life skills program through PIK-R contributes to the development of students’ emotional intelligence, which serves as a foundation for strengthening moral intelligence and character within the school context.